Identification of the 5′-Terminal Packaging Signal of the H1N1 Influenza A Virus Neuraminidase Segment at Single-Nucleotide Resolution - Seshimo, Erika; Momose, Fumitaka; Morikawa, Yuko (Frontiers in Microbiology, 2021)
The genome of the influenza A virus is an eight-segmented negative-strand RNA (vRNA). Progeny vRNAs replicated in the nucleus selectively assemble into a single set of eight different segments, probably in the cytoplasm, and are packaged into progeny virions at the cell membrane. In these processes, a region of approximately 100 nucleotides at both ends of each segment is thought to function as a selective assembly/packaging signal; however, the details of the mechanism, such as the required sequences, are still unknown. In this study, we focused on the 5'-terminus of the sixth neuraminidase gene segment vRNA (Seg.6) to identify the essential sequence for selective packaging. The 5'-terminal region of the A/Puerto Rico/8/34 strain Seg.6 was divided into seven regions of 15 nucleotides each from A to G, and mutations were introduced into each region by complementary base substitutions or synonymous codon substitutions. Mutant viruses were generated and compared for infectious titers, and the relative ratios of the eight segments packaged into virions were measured. We also ascertained whether mutant vRNA was eliminated by competitive packaging with wild-type vRNA. Mutations in the A–C regions reduced infectious titers and eliminated mutant vRNAs by competition with wild-type vRNA. Even under noncompetitive conditions, the packaging efficiency of the A or B region mutant Seg.6 was reduced. Next, we designed an artificial vRNA with a 50-nucleotide duplication at the 5'-terminal region. Using this, a virus library was created by randomly replacing each region, which became an untranslated region, with complementary bases. After selecting proliferative viruses from the library, nine wild-type nucleotides in the A and B regions were identified as essential bases, and we found that these bases were highly conserved in Seg.6 vRNAs encoding the N1 subtype neuraminidase. From these results, we conclude that the identified bases function as the 5'-terminal packaging signal for the N1 subtype Seg.6 vRNA.